(untitled) - Garraty, John Arthur (New York, 1998)
This volume is a comprehensive political history of the American nation which integrates social, economic and cultural developments in a single treatment. This edition has been updated to include Newt Gingrich's Contract with America, the 1996 election and the 1995 budget crisis.
Keywords: United states,Hoa Kỳ; History,Lịch sử